Metabolic and transcriptional elucidation of the carotenoid biosynthesis pathway in peel and flesh tissue of loquat fruit during on-tree development - Hadjipieri, Margarita; Georgiadou, Egli C.; Marin, Alicia; Diaz-Mula, Huertas M.; Goulas, Vlasios; Fotopoulos, Vasileios; Tomás-Barberán, Francisco A.; Manganaris, George A. (My University, 2017)
Background: Carotenoids are the main colouring substances found in orange-fleshed loquat fruits. The aim of this study was to unravel the carotenoid biosynthetic pathway of loquat fruit (cv. 'Obusa') in peel and flesh tissue during distinct on-tree developmental stages through a targeted analytical and molecular approach. Results: Substantial changes regarding colour parameters, both between peel and flesh and among the different developmental stages, were monitored, concomitant with a significant increment in carotenoid content. Key genes and individual compounds that are implicated in the carotenoid biosynthetic pathway were further dissected with the employment of molecular (RT-qPCR) and advanced analytical techniques (LC-MS). Results revealed significant differences in carotenoid composition between peel and flesh. Thirty-two carotenoids were found in the peel, while only eighteen carotenoids were identified in the flesh. Trans-lutein and trans-beta-carotene were the major carotenoids in the peel; the content of the former decreased with the progress of ripening, while the latter registered a 7.2-fold increase. However, carotenoid profiling of loquat flesh indicated trans-acryptoxanthin, followed by trans-beta-carotene and 5,8-epoxy-beta-carotene to be the most predominant carotenoids. High amounts of trans-beta-carotene in both tissues were supported by significant induction in a chromoplast-specific lycopene beta-cyclase (CYCB) transcript levels. PSY1, ZDS, CYCB and BCH were up-regulated and CRTISO, LCYE, ECH and VDE were down-regulated in most of the developmental stages compared with the immature stage in both peel and flesh tissue. Overall, differential regulation of expression levels with the progress of on-tree fruit development was more evident in the middle and downstream genes of carotenoid biosynthetic pathway. Conclusions: Carotenoid composition is greatly affected during on-tree loquat development with striking differences between peel and flesh tissue. A link between gene up-or down-regulation during the developmental stages of the loquat fruit, and how their expression affects carotenoid content per tissue (peel or flesh) was established.
Keywords: Eriobotrya japonica; Developmental stages; Maturation; Ripening; Beta-carotene; Beta-cryptoxanthin; Lutein; LC-MS; Biosynthetic pathway